P-Glycoprotein-Mediated Efflux Using a Rapidly Maturing Caco2 Clone (CLEFF4) in Only 5 Days without Requiring Modified Growth Medium. (January 2021) - Crowe, Andrew
In drug discovery it is essential that one of the parameters tested for any new chemical entity is its affinity for human efflux systems, most notably P-glycoprotein (P-gp). These efflux systems affect not only rates of oral absorption but also rates of excretion through the liver, blood–brain barrier, and accumulation in potential target cells that upregulate efflux systems. Current methods to determine drugs' P-gp transport potential include in vitro bidirectional transport studies, and the two most common cell lines used are Caco2 and MDR1-transfected MDCK models. Caco2 cells are human but slow growing and require more than 3 weeks to mature, while MDCK cells are canine, but when transfected with human P-gp become a rapid model of P-gp affinity. Our laboratory has generated a Caco2 subclone called CLEFF4 that is fully human, yet now approaches the rapid nature of the MDCK model. No special medium is required. We have shown, in as little as 5 days postseeding, high transepithelial electrical resistance values of more than 1000 Ω·cm 2 plus P-gp expression more than threefold higher than that of 21-day-old cells. Currently tested drugs included rhodamine 123 (Rh123), vinblastine, and doxorubicin, and all drugs exhibited P-gp-mediated efflux that was inhibited by PSC833. By day 6, bidirectional transport of Rh123 was as potent as that of mature Caco2 cells, for use in comparative P-gp affinity studies. We now have a human P-gp model that is rapid and works without any need for special accelerating medium. We believe this could be a welcome addition to the testing regime of new chemical entities.